Knowledge and perception of a clinical trial among the participants: An experience from oral cholera vaccine study in Koshi Province, Nepal - Shipra Chaudhary; Surendra Uranw; Basant Rai; Nisha Keshary Bhatta; Gauri Shankar Shah; Prakash Poudel; Basudha Khanal; Rosan Prasad Shah Kalawar; Nikita Rai; Jenisha Shrestha; Merina Shrestha; Shalu Parajuli; et al. (Taylor & Francis Group, 2024)
Clinical trials (CT) have been the cornerstones in developing medicines, vaccines, and new interventions. Despite tremendous efforts, a CT cannot succeed without participants' involvement. Various factors can affect people's attitude and participation in a CT. Hence, this study was conducted to assess the knowledge and perception of a clinical trial among the participants of a CT at B.P. Koirala Institute of Health Sciences, Dharan, Nepal. This was a population-based descriptive cross-sectional study conducted during 2021-2022. Participants involved in a phase III clinical trial were enrolled, and an in-depth interview was conducted using a semi-structured questionnaire. Demographic information, knowledge and perception about CT were assessed, and a descriptive analysis was done. Among 622 participants, the majority were males (321; 51.6%), literate (587; 94.37%), of indigenous ethnic groups (Janajatis 61.4%), and without previous experience of CT (504; 81.1%). The majority had adequate knowledge (566/622; 91%) and positive perception (595/622; 95.7%) of CT. Most participants (467; 75.1%) had participated in CT to get protection from the particular disease from the provided vaccine and (603; 96.9%) believed CT to benefit mankind. Further studies comparing pre- and post-participation knowledge and perception might be helpful for planning and better management of CTs in such settings.